Mathematical Programming as a management tool in micro and small companies: a proposal for decision support in the clothing sector - Santos, Diego Vieira dos; Gomes, Keydson Quaresma; Rocha, Alessandro Roberto; Zatta, Fernando Nascimento; Mattos, Aliomar Lino; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2021)
In an environment of economic instability, the search for strategies that guarantee the enterprise survivor has driven Micro and Small Enterprises (SMEs) in Brazil to assume a more agile posture in decision-making. Thus, this study aimed to prepare a proposal to assist decision making – focused on production and operations management – of a company in the apparel sector using Linear Programming (LP). Data collection and application of the methodology were directed to an MPE located in the region of Vale do Rio Doce (Minas Gerais). The development of the solution took place through the primary programming language. The results allowed, in addition to subsidizing decisions, parameterizing the solution for everyday needs. The deterministic model presented in this case proved to be an effective tool to deal with business and production management issues, especially with regard to optimal resource allocation, which can and should be adapted to different scenarios and conditions.
Keywords: Business forecasting; Optimization of processes; Cost management; Trend analysis.